Relationship between Entrepreneurial Characteristics and Entrepreneurial Intention among Community College Students: Mediating Role of Entrepreneurial Knowledge - Kasturee Bhai, Arumugam Rasammah (2023)
The low rate of community college graduates' involvement in entrepreneurship in Selangor has prompted this research to investigate the factors influencing their entrepreneurial intentions. This research is particularly important given the pressing need to generate economic growth through younger generations amidst an aging population, which presents a critical challenge to Selangor, and Malaysia. Moreover, Selangor's strong government support for entrepreneurship, exemplified by initiatives like the Selangor Youth Community and Entrepreneurship Selangor, plays a crucial role in fostering the entrepreneurial ecosystem. By conducting a detailed analysis of entrepreneurial intentions in Selangor, we aim to identify the factors impacting community college students and inform targeted interventions and policy measures. To achieve this, present study assesses the relationship between entrepreneurial characteristic dimensions (risk-taking and fear of failure) and community college student’s entrepreneurial intention. The study also examined the mediating role of entrepreneurial knowledge in the relationship. In order to gather data, a sample of 580 respondents was selected from ten community colleges in Selangor. Final data analysis was conducted on 358 respondents using simple random sampling, and adopted questionnaires were employed for data collection. Descriptive and inferential statistical analysis techniques were employed to examine a total of seven hypotheses, comprising five direct relationship hypotheses and two indirect relationship hypotheses. Four out of the five direct relationships were supported, with one being unsupported. Regarding the indirect relationship, the study found that entrepreneurial knowledge partially mediates the relationship between risk-taking and entrepreneurial intention. However, no mediation was observed in the relationship between fear of failure and entrepreneurial intention. The findings offer partial support for the Theory of Planned Behaviour, aligning with the theory's predictions on risk taking and entrepreneurial knowledge while revealing a contradiction in relation to the fear of failure. The study underscores the significance of promoting entrepreneurial knowledge among community college students as a means to cultivate their intentions and behaviours pertaining to entrepreneurship. Additionally, it offers practical contributions and implications. Furthermore, it acknowledges limitations and provides recommendations and suggestions for future research, which can benefit the Ministry of Higher Education Malaysia, community college management, lecturers and teachers, students, and society.